Bravo Two Zero - McNab, Andy, 1959- (London Bantam Press, 1993)
McNab's account of an SAS mission in which he led an eight-man patrol deep behind enemy lines in the Gulf War. It is a chronicle of courage, endurance and dark humour in circumstances for which McNab and his men became what is believed to be the most highly decorated patrol since the Boer War.
Include Glossary, Maps and Illustration
Keywords: Persian Gulf War (1991) -- Great Britain. Army. Special Air Service -- Great Britain. Army. Special Air Service Regiment, 22nd